Rekayasa Modularity pada Sepeda Anak Usia Dini dengan Empat Konfigurasi - kurniawan, arie -; Gede Cakra Kandayana, Anak Agung (Aliansi Desainer Produk Industri Indonesia (ADPII), 2025)
Early childhood bikes are products that support children's development through physical activity and creativity stimulation. Currently, the market offers various types of early childhood bicycles with varied designs and functions, but very few have multi-configuration features. This research aims to formulate and develop a children's bicycle design based on modularity system engineering. This approach produces designs in the form of modular units that can be assembled into various types of bicycles. The method used in this research is Integrated Digital Design, with the development of a bicycle frame module that meets the principles of modularity. This modular design considers four main aspects: (1) bicycle geometry, (2) module units, (3) integration between units, and (4) configuration engineering. System modularity engineering allows early childhood bicycles to have four different configurations, thus providing a more varied play experience, developmental stimulation, and increasing children's creativity.